2015
DOI: 10.1186/s13568-015-0121-8
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous bioethanol distillery wastewater treatment and xylanase production by the phyllosphere yeast Pseudozyma antarctica GB-4(0)

Abstract: Bioethanol production using lignocellulosic biomass generates lignocellulosic bioethanol distillery wastewater (LBDW) that contains a large amount of xylose, making it a potential inexpensive source of xylose for biomaterials production. The main goal of this study was the production of useful enzymes from LBDW during treatment of this wastewater. In this study, we found that xylose strongly induced two yeast strains, Pseudozyma antarctica T-34 and GB-4(0), to produce novel xylanases, PaXynT and PaXynG, respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…This result suggested that PaE expression and/or secretion decreased with defective MEL production. On the other hand, strain GB-4(0) secretes large amounts of 33-kDa endo-β-xylanase in the presence of xylose (Watanabe et al 2015). We observed similar signal intensity corresponding to xylanase in the culture supernatants of ΔPa EMT1 and wild-type cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This result suggested that PaE expression and/or secretion decreased with defective MEL production. On the other hand, strain GB-4(0) secretes large amounts of 33-kDa endo-β-xylanase in the presence of xylose (Watanabe et al 2015). We observed similar signal intensity corresponding to xylanase in the culture supernatants of ΔPa EMT1 and wild-type cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, secretome analysis of Kalmonozyma brasiliensis grown on distinct sources of carbon helped in identifying 20 CAZymes (13 GHs, 3 CEs and 4AAs), which can have significant biotechnological potentials [ 126 ]. Two strains of Moesziomyces antarcticus was shown to produce xylanase of 33 kDa and belonged to GH10 family [ 127 ], while M. aphidis strain was shown that the yeast produces amylase that catalyzes endohydrolysis of 1,4-α-D-glycoside linkage in polysaccharides [ 128 ]. Pectin degrading activity was identified in Moesziomyces antarcticus , Kalmonozyma fusiformata and Pseudozyma sp.…”
Section: Microbial Strain Engineering Of Filamentous Fungi Yeast Andmentioning
confidence: 99%
“…This strain was found to produce thermostable endoxylanase and beta-xylosidase. The beta-xylosidase was optimally active at pH 7.0 and 60 • C, while the endoxylanase was active over a broad range of pH (5.0-10.0) and temperatures ( Considering the Antarctic biodiversity, in literature, there are several examples of fungi able to produce cold-adapted xylanase [56] or examples of Antarctic yeast able to use as cheaper growth media the lignocellulosic bioethanol distillery wastewater, which contains a large amount of xylose, and concurrently able to produce endo-β-xylanases [57]. As regards the Antarctic bacterial microorganisms possessing xylanase activity, recently, a new haloalkaliphilic, non-endospore-forming actinobacterium, named Nesterenkonia aurantiaca, was isolated from a soil sample, collected at Cape King (Antarctica) [58], and it was found to be able to hydrolyse xylan on an agar plate.…”
Section: Xylanase and β-Xylosidasementioning
confidence: 99%